THE INFLUENCE OF FINANCIAL TECHNOLOGY ON THE FINANCIAL BEHAVIOR OF SATYAGAMA UNIVERSITY STUDENTS - I Nyoman Suri Adnyana; Rahmatullah Rahmatullah; Didi Sukardi; Murdiyono Murdiyono (Yayasan Nusantara Hasana Berdikari, 2023)
The development of digital technology has driven the increasing use of financial technology (fintech) services among students, particularly in digital payment transactions, savings, and investments. This study aims to determine the influence of financial technology on the financial behavior of Satyagama University students. The research method used a quantitative approach by distributing questionnaires to Satyagama University students as research respondents. The results show that the use of financial technology has a positive influence on student financial behavior, particularly in terms of ease of financial management, transaction efficiency, and increased awareness in managing expenses. Although there is a tendency for consumptive behavior if fintech use is not properly controlled.